A Review of Central Bank Digital Currencies - Singh, Amitoj; Parapallicherayil John, David; Pattamookkil Jacob, Arun (Ushus Journal of Business Management, 2022)
This is a review paper on the exploratory research done by various central banks and international organisations on CBDCs and the framework to be followed for implementing these CBDCs so that the monetary system of a specific country remains unaffected. CBDCs and cryptocurrency in general as we know have become quite popular and are the talking point for many research scholars, economists and investment analysts. While many believe cryptocurrencies to have no intrinsic value, the value of the underlying technology i.e blockchain is something that can be argued upon. CBDCs remove the major cons of cryptocurrency by providing stability to the volatile cryptocurrency market and by acting as a legal tender thereby gaining the trust of retail public. Many governments believe that the introduction of CBDCs into the economy could simplify the payment’s structure thereby increasing the velocity of money leading to higher GDP growth. But one possibility that shatters this glass of optimistic views is the possibility of disintermediation of banks which could adversely affect the credit creation capacity of the country and disintegrate the entire monetary policy formation mechanism. Therefore, though the concept of digital currencies may excite many people, its adoption in an economy should be considered only after thorough research and pilot programs conducted by the central banks.